Recurrence of Hamstring Injuries and Risk Factors for Partial and Complete Tears in the National Football League: An Analysis From 2009–2020. Issue 2 (4th March 2023) - Bodendorfer, Blake M.; DeFroda, Steven F.; Newhouse, Alexander C.; Yang, Daniel S.; Shu, Henry T.; Wichman, Daniel; Murphy, Jordan P.; Milner, John D.; Hartnett, Davis A.; Gould, Heath; Chahla, Jorge; Nho, Shane J.
ABSTRACT: Purpose: To (1) characterize hamstring injury (HSI) recurrence rates across the 2009–2010 to 2019–2020 NFL seasons and (2) to identify HSI recurrence risk factors among positions and determine the weekly return to play (RTP) recurrence risk. We hypothesized that older players, skill position players, and players returning to play faster were most at risk. Methods: Public data from the 2009–2010 to 2019–2020 seasons were reviewed to identify HSIs. Player characteristics were collected before and two seasons following injury. A week-by-week analysis of recurrence risk was evaluated with linear and logarithmic trendlines of the best fit. Results: A total of 2075 HSI were identified with a mean age of 26.2 years (20.0–43.0), BMI of 29.6 (22.7–43.5), and 3.4 seasons of experience (0–17), with 1826 strains (88.0%), 236 partial tears (11.3%), and 13 complete tears (0.63%). Of the 2075 injuries, 796 (38.4%) were recurrent, with 247 (11.9%) being a same-season reinjury. Logistic regression found that fewer weeks before RTP, in-game injury, and lower BMI were risk factors for same-season recurrence. For any recurrence, logistic regression identified more recent year of injury, lower BMI, and longer playing experience as significant risk factors. Wide receivers were found to be at risk for same-season recurrence. For any-season recurrence, defensive backs, linebackers, running backs, tight ends, and wide receivers were at risk. Week-by-week recurrence analysis determined the greatest risk to be when players returned within 2 weeks (13.4%). Conclusions: There is a high rate of HSI recurrence in the NFL. Risk factors for same-season injury include shorter time to RTP, in-game injury, lower BMI, and playing wide receiver. Risk factors for any-season recurrence were more recent year of injury, lower BMI, longer playing experience, and playing defensive back, linebacker, running back, tight end, or wide receiver. The greatest risk factor for HSI recurrence was RTP within 2 weeks.